Effect of knee braces on balance ability wearing ski boots (a pilot study) - Bottoni, G.; Kofler, P.; Hasler, M.; Giger, A.; Nachbauer, W. (Procedia Engineering, 2014)
In the literature it is mentioned that ski boots might decrease balance ability and this increases injury risk. The use of knee braces during skiing might help in knee stabilization and, therefore, improve balance ability. Eight female sport students participated in this study (age 24.88±2.1 years; BMI 21.6±1.97). Four knee supports were tested: the first (B1) was a soft knee sleeve with a reinforcement around the patella and two thin flexible metal bars for the lateral stabilization; the second (B2) was a neoprene sleeve with thin flexible metal bars for the lateral stabilization; the third (B3) was an elastic brace with double-joint metallic bars for the lateral stabilization, a reinforcement and a hole around the patella and fixation straps; the fourth (B4) was a massive knee brace with a more rigid structure ideated to return to sport after injury. The balance ability test was performed using the MFT-S3 Check System. The test was repeated five times, one without knee brace and one with each type of knee brace, in randomized order. Wearing the B3 a worsening in balance ability in comparison with the condition without brace was found. Wearing B2 the stability index (symmetry of the platform movement) in the anterior-posterior direction was significantly better than wearing the more cumbersome braces B3 and B4. No significant differences between the conditions were detected for the balance ability in the medio-lateral direction. From this pilot study it is possible to conclude that knee braces might influence balance ability wearing ski boots.